The Dynamic Correlation Between Oil Price, Exchange Rate and Stock Market: Evidence from Major Emerging Oil-Importing and Oil-Exporting Countries - Yao, Jundai (2016)
This paper examines the impact of crude oil price and exchange rate on stock market for oil importing and oil exporting emerging economies from July 2006 to August 2016 with VAR, Granger Causality, VECM model and ARCH system. The result implies that exchange rate and oil price are negatively correlated with stock market in India, while the positive correlation is observed in Saudi Arabia. Such corresponding is not shown to be significant in China and Russia. In addition, statistical result does not present any significant asymmetric effect in four markets.